PENGUATAN TATA KELOLA KELEMBAGAAN IAIN MENUJU IAIN AMBON BERMUTU MELALUI PELAKSANAAN GOOD UNIVERSITY GOVERNANCE - Abd. Jabar Abdul (TAHKIM, 2018)
The data collection was done by using; documentation, observation, and interviews. Data were analyzed qualitatively through data reduction, display/presentation of data, and conclusion/verification. The results showed that; 1) governance institutions in the implementation of Ambon IAIN Tridarma not running optimally and satisfactorily. The fundamental issue is due to weak work culture, the lack of consolidation and utilization of academic resources, and lack of commitment, awareness and a sense of collective responsibility to understand, appreciate and execute the vision, mission, tasks, functions and programs are consistently under applicable laws; 2) Application of the principles of good university governance in institutional governance as a whole is still relatively weak. Indication of the weakness was seen; a) the lack of transparency, especially in terms of regulation, management and implementation of the budget; b) Accountability in terms of public accountability which demands an increase in PT's ability to maximize available resources effectively and efficiently to achieve the expected results, in this context IAIN not sufficiently accountable; c) Responsibility is still relatively weak, many neglected issues, the activities and performance of quality not still often done repeatedly so IAIN not yet reached the high quality; d) Independence, space for creating, innovating is open to all parties, the problem is the individual consciousness academicians who have maximum independence in utilizing space to develop professionalism, except to the work that are routine, structural and formalistic; e) Fairness or equality in relation to the consolidation and utilization of academic resources to participate in various academic agenda has not seen enough fairness. 3) Quality IAIN Ambon is currently in the category of good or moderate. The achievement of quality is closely related to the level of implementation of the principles of GUG that are not yet consistent and maximum. If the principles of GUG can be consistently and maximum, it is believed to be able to make IAIN Ambon superior, high-quality, competitively and have high competitiveness.